The complete works of Rev. Andrew Fuller: with a memoir of his life, by Andrew Gunton Fuller : reprinted from the third London edition - Fuller, Andrew (American Baptist Publication Society, 1845)
v. 1. Memoirs, sermons, etc.--v. 2. Gospel its own witness-controversial publications.--v. 3. Expositions-miscellaneous.